A kind of BaSO 4 -TiO 2 Composite powder and preparation method thereof

By forming a porous structure on the surface of BaSO4 powder and depositing TiO2, the problem of insufficient binding force between TiO2 and mineral carrier is solved, and the stability and application effect of the composite powder are significantly improved.

CN118925753BActive Publication Date: 2025-03-21JIANGSU QUNXIN POWDER TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410994873.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-03-21
Estimated Expiration
2044-07-24

AI Technical Summary

Technical Problem

In the existing TiO2 composite powder, the interface bonding force between TiO2 and the mineral carrier is insufficient, resulting in easy peeling of TiO2 during use, affecting the application effect.

Method used

By partial reduction reaction of BaSO4 powder under high temperature hydrogen atmosphere, a porous BaSO4 powder is formed, and TiO2 is deposited on its surface by hydrolyzing precipitation, enhancing the interface binding force of the two.

Benefits of technology

It improves the stability and practical application effect of BaSO4-TiO2 composite powder, ensures that TiO2 is not easy to fall off during use, and enhances mechanical properties and structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004959865040000141
    Figure BDA0004959865040000141
Patent Text Reader

Abstract

The present invention relates to the technical field of new materials, and specifically proposes a BaSO4-TiO2 composite powder and a preparation method thereof, comprising first subjecting the BaSO4 powder to hydrogen doping treatment, then preparing a BaSO4 suspension, adding a TiOSO4 aqueous solution to the BaSO4 suspension for mixing, adjusting the pH of the mixed system to 2-4, aging at 70-90°C for 3-8h after stirring, aging at 20-30°C for 2-6h, centrifuging, washing, and drying after the reaction is completed to obtain a precursor, wherein the mass ratio of TiOSO4:BaSO4 is 1:(5-8); the precursor is roasted in a muffle furnace to obtain a BaSO4-TiO2 composite powder. The present invention obtains a BaSO4-TiO2 composite powder with good structural stability by using pretreated BaSO4 powder, so that the composite powder also has good stability under complex use environments, and improves the application effect of the composite powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to a BaSO4-TiO2 composite powder and a preparation method thereof. Background Art

[0002] TiO2 is an important industrial raw material. TiO2 of different particle sizes has different physical and chemical properties and different application fields. Submicron TiO2 is called titanium dioxide, which has important applications in industries such as pigments, coatings, inks, papermaking, plastics and rubber, chemical fibers, and ceramics. Nano-TiO2 has excellent photocatalytic properties and has broad application prospects in the fields of degradation of organic pollutants, air purification, decomposition of water and hydrogen production. However, the current price of TiO2 is relatively high, which limits the application of TiO2 to a certain extent. In addition, nano-TiO2 also has serious agglomeration phenomenon, low utilization rate, difficulty in recycling and reuse, and easy to cause secondary pollution. Researchers have conducted in-depth research on the above problems and proposed a variety of solutions. Among them, loading TiO2 on the surface of micron-sized inorganic mineral carriers to prepare mineral-TiO2 composite powders has been proven to be an effective strategy. This method can not only reduce costs, but also improve the dispersibility of nano-TiO2, improve its utilization rate, and increase the reactive sites. In addition, the particle size and mass of the inorganic mineral carrier powder are relatively large. After nano-TiO2 is loaded on its surface to form a composite powder, it can be separated from the reaction solution by simple centrifugation, so that it can be recycled and reused to avoid secondary pollution.

[0003] After years of research, a variety of methods for preparing mineral-TiO2 composite powders have been developed. These preparation methods are mainly divided into two types: (i) using commercially available titanium dioxide or nano-TiO2 as a titanium source, using mechanochemistry, hydrophobic aggregation and other methods to load TiO2 on the surface of an inorganic mineral carrier to prepare a mineral-TiO2 composite powder; (ii) using chemical reagents such as butyl phthalate and titanium tetrachloride as a titanium source, using sol-gel, hydrothermal and other methods to load TiO2 on the surface of an inorganic mineral carrier to form a mineral-TiO2 composite powder. However, the current research direction mainly focuses on the controllability of the particle size of TiO2 loaded in the composite powder. However, in the actual application process, there is a problem of insufficient interfacial bonding between TiO2 and minerals, which may cause TiO2 to peel off from the carrier surface during use, ultimately affecting its actual application effect. Summary of the invention

[0004] In view of this, the present invention proposes a BaSO4-TiO2 composite powder with a more stable surface composite structure and more reliable interface bonding and a preparation method thereof.

[0005] In a first aspect, the present invention provides a method for preparing a BaSO4-TiO2 composite powder, the method comprising the following steps:

[0006] Step 1: Heat the BaSO4 powder to 600-800°C and keep it warm for 2-4 hours in a hydrogen atmosphere to obtain gas-doped BaSO4 powder;

[0007] Step 2: prepare the gas-doped BaSO4 powder into a BaSO4 suspension, add the TiOSO4 aqueous solution into the BaSO4 suspension and mix, adjust the pH of the mixed system to 2-4, stir and age at 70-90°C for 3-8h, and age at 20-30°C for 2-6h, centrifuge, wash and dry after the reaction to obtain a precursor, wherein the mass ratio of TiOSO4:BaSO4 is 1:(5-8);

[0008] Step 3: calcine the precursor in a muffle furnace to obtain BaSO4-TiO2 composite powder.

[0009] In the above implementation mode, BaSO4 powder undergoes a partial reduction reaction in a high-temperature hydrogen atmosphere to generate barium sulfide. At the same time, the diffusion and reaction of hydrogen will form microscopic holes on the surface of the BaSO4 powder. The holes formed by the diffusion and reaction of hydrogen are conducive to more stable loading of titanium dioxide on the surface of the BaSO4 powder, increasing the interfacial bonding force between the two, ensuring that titanium dioxide in the composite powder will not fall off easily during use, thereby improving the stability of the composite powder and the actual application effect.

[0010] In some embodiments, in step 1, before heating the BaSO4 powder, the step further includes dispersing the BaSO4 powder in an ethanol solution of 3-chloropropyltriethoxysilane, stirring the reaction for 1-2 hours, and then drying to obtain the treated BaSO4 powder.

[0011] In the above implementation mode, the surface structure of BaSO4 powder is irregular. Directly using BaSO4 powder for heating and penetration reaction in hydrogen atmosphere may cause uneven surface or excessive pore formation of BaSO4 powder, which will cause the strength of BaSO4 powder to decrease and affect the application effect of composite powder. In order to overcome this problem as much as possible, 3-chloropropyltriethoxysilane is used to form a coating structure on the surface of BaSO4 powder. 3-Chloropropyltriethoxysilane is a silane coupling agent containing triethoxysilane group and chloropropyl group in its molecular structure. In organic solvents such as ethanol, triethoxysilane group can undergo hydrolysis and condensation reaction with hydroxyl group on the surface of barium sulfate powder to form siloxane bond. At the same time, chloropropyl group is attached to the surface of barium sulfate powder, finally forming a uniform coating layer, thereby improving the surface chemical activity and affinity of the powder. In the presence of the coating, the evenly distributed chloropropyl groups introduce additional active sites, promoting the uniform reaction of hydrogen on the surface of the BaSO4 powder to form a uniform pore structure. At the same time, the presence of the coating improves the wettability and gas diffusivity of the BaSO4 powder surface, which helps hydrogen diffuse more evenly to the entire particle surface at high temperatures, thereby promoting the formation of uniform pores. Moreover, the presence of the coating can also protect the surface of the BaSO4 powder, avoid excessive thermal decomposition and agglomeration, buffer temperature changes, reduce thermal stress, and further ensure the stability and uniformity of the pore structure.

[0012] In some embodiments, the mass concentration of the ethanol solution of 3-chloropropyltriethoxysilane is 1-2%.

[0013] In the above embodiment, the concentration range of 1-2% can provide an appropriate solution viscosity to ensure that 3-chloropropyltriethoxysilane is evenly dispersed in ethanol. Too low a concentration may cause the solution to be too thin and the coating effect to be poor; too high a concentration may cause the solution to be too viscous and difficult to coat evenly. At a concentration of 1-2%, the hydrolysis and condensation reaction rates of 3-chloropropyltriethoxysilane are moderate, and a uniform siloxane coating can be formed on the surface of BaSO4 powder. Higher concentrations may accelerate the reaction rate, but may result in uneven coating thickness; lower concentrations will result in a slower reaction rate and the coating may be incomplete.

[0014] In some embodiments, in step one, after the insulation reaction, the BaSO4 powder is heated to 700-900°C in a muffle furnace, kept warm for 2-4 hours, then cooled to 30°C at 3-4°C / min, washed with deionized water and dried at 60-80°C to obtain gas-doped BaSO4 powder.

[0015] In the above embodiment, further calcination can ensure that the formed pore structure is further stabilized, and at the same time, the residual organic solvent and unreacted 3-chloropropyltriethoxysilane are volatilized to ensure the purity of the powder surface. Slow cooling can eliminate thermal stress and ensure the integrity of the pores and the surface structure of BaSO4 powder.

[0016] In some embodiments, in step 2, the BaSO4 suspension is obtained by mixing BaSO4 and water in a mass ratio of 1:(20-40), heating to 70-90°C, and adjusting the pH to 2-4.

[0017] In some embodiments, in step 2, the TiOSO4 aqueous solution is obtained by mixing and stirring TiOSO4 and water in a mass ratio of 1:(100-120).

[0018] In some embodiments, in step 2, after adjusting the pH of the mixed system to 2-4, stirring is performed for 1-3 hours before aging.

[0019] In some embodiments, in step three, the calcination temperature is 600-900° C., and the calcination time is 2 hours.

[0020] In a second aspect, the present invention also provides a BaSO4-TiO2 composite powder prepared by the above-mentioned preparation method.

[0021] In a third aspect, the present invention also provides an application of the BaSO4-TiO2 composite powder prepared by the above preparation method in the field of photocatalysts or pigments.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention provides a BaSO4-TiO2 composite powder with better surface titanium dioxide adhesion stability. The surface of barium sulfate powder is pre-treated by gas doping pore making to obtain porous barium sulfate powder, and then titanium dioxide is precipitated on the surface of the barium sulfate powder by hydrolysis precipitation coating. The composite powder obtained by the method not only solves the problems of high agglomeration and poor dispersibility of nano-scale titanium dioxide, but also has strong bonding force between titanium dioxide and barium sulfate, has better mechanical properties and structural stability, and can maintain the stability of the composite structure in different usage scenarios, thereby providing good application effects. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0026] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0027] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0028] In the prior art, although the high cost and easy agglomeration of titanium dioxide can be overcome by preparing composite powders, the bonding strength between the core minerals and the shell titanium dioxide in the composite powder is insufficient, which will lead to the separation of titanium dioxide and core minerals in some complex application scenarios, or during transportation or post-processing. This will affect the uniformity of the composite powder. At the same time, the separated titanium dioxide is prone to agglomeration, and the exposed core minerals after separation are easily corroded, which will reduce the overall life of the composite powder, deteriorate the use effect, and lack reliability. At the same time, this structurally unstable composite powder is not conducive to recycling and processing, and is prone to unnecessary material loss.

[0029] Therefore, BaSO4-TiO2 composite powders with high structural stability can significantly improve material performance in applications and overcome various problems caused by unstable powder structures. This includes improving dispersibility, enhancing mechanical strength and durability, improving photocatalytic efficiency, improving coating and pigment performance, improving sunscreen and antibacterial effects, and simplifying processing and recycling processes. By ensuring the structural stability of the composite powder, more efficient, longer-lasting and more reliable material applications can be achieved to meet the needs of various industrial and consumer products.

[0030] Example 1

[0031] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0032] Preparation method:

[0033] S1. Add BaSO4 powder into a high-temperature furnace, set the furnace temperature to 700℃, maintain the hydrogen flow rate at 100mL / min, keep the reaction at this temperature for 3h, and then cool it down to 30℃ at 4℃ / min to obtain gas-doped BaSO4 powder.

[0034] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0035] S3. Calcine the precursor at 700° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0036] Example 2

[0037] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0038] Preparation method:

[0039] S1. Add BaSO4 powder into a high-temperature furnace, set the furnace temperature to 600℃, maintain the hydrogen flow rate at 100mL / min, keep the reaction for 4h, and cool down to 30℃ at 4℃ / min to obtain gas-doped BaSO4 powder.

[0040] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0041] S3. Calcine the precursor at 700° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0042] Example 3

[0043] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0044] Preparation method:

[0045] S1. Add BaSO4 powder into a high-temperature furnace, set the furnace temperature to 800℃, maintain the hydrogen flow rate at 100mL / min, keep the reaction at this temperature for 2h, and then cool it down to 30℃ at 3℃ / min to obtain gas-doped BaSO4 powder.

[0046] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0047] S3. Calcine the precursor at 700° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0048] Example 4

[0049] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0050] Preparation method:

[0051] S1. Add BaSO4 powder into a high-temperature furnace, set the furnace temperature to 700℃, maintain the hydrogen flow rate at 100mL / min, keep the reaction at this temperature for 3h, and then cool it down to 30℃ at 4℃ / min to obtain gas-doped BaSO4 powder.

[0052] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:30, heat to 90°C, and adjust the pH to 2 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:110 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 2, stir for 1 hour, and age at 70°C for 8 hours and at 30°C for 2 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:8.

[0053] S3. Calcine the precursor at 700° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0054] Example 5

[0055] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0056] Preparation method:

[0057] S1. Add BaSO4 powder into a high-temperature furnace, set the furnace temperature to 700℃, maintain the hydrogen flow rate at 100mL / min, keep the reaction at this temperature for 3h, and then cool it down to 30℃ at 4℃ / min to obtain gas-doped BaSO4 powder.

[0058] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:40, heat to 70°C, and adjust the pH to 4 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:120 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 4, stir for 3 hours, and age at 90°C for 3 hours and at 20°C for 6 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:5.

[0059] S3. Calcine the precursor at 700° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0060] Example 6

[0061] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0062] Preparation method:

[0063] S1. Add BaSO4 powder into a high-temperature furnace, set the furnace temperature to 700℃, maintain the hydrogen flow rate at 100mL / min, keep the reaction at this temperature for 3h, and then cool it down to 30℃ at 4℃ / min to obtain gas-doped BaSO4 powder.

[0064] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0065] S3. Calcine the precursor at 600° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0066] Example 7

[0067] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0068] Preparation method:

[0069] S1. Add BaSO4 powder into a high-temperature furnace, set the furnace temperature to 700℃, maintain the hydrogen flow rate at 100mL / min, keep the reaction at this temperature for 3h, and then cool it down to 30℃ at 4℃ / min to obtain gas-doped BaSO4 powder.

[0070] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0071] S3. Calcine the precursor at 800° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0072] Example 8

[0073] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0074] Preparation method:

[0075] S1. Add BaSO4 powder into a high-temperature furnace, set the furnace temperature to 700℃, maintain the hydrogen flow rate at 100mL / min, keep the reaction at this temperature for 3h, and then cool it down to 30℃ at 4℃ / min to obtain gas-doped BaSO4 powder.

[0076] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0077] S3. Calcine the precursor at 900° C. for 2 h in a muffle furnace to obtain BaSO4-TiO2 composite powder.

[0078] Example 9

[0079] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0080] Preparation method:

[0081] S1. Disperse BaSO4 powder in an ethanol solution of 3-chloropropyltriethoxysilane with a mass concentration of 2%, stir and react for 1 hour, filter, and dry at 75°C to obtain treated BaSO4 powder. Add the treated BaSO4 powder into a high-temperature furnace, set the furnace temperature to 700°C, maintain the hydrogen flow rate at 100mL / min, keep the reaction warm for 3 hours, and cool down to 30°C at 4°C / min to obtain gas-doped BaSO4 powder.

[0082] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0083] S3. Calcine the precursor at 700° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0084] Example 10

[0085] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0086] Preparation method:

[0087] S1. Disperse BaSO4 powder in an ethanol solution of 3-chloropropyltriethoxysilane with a mass concentration of 1%, stir and react for 2 hours, filter, and dry at 75°C to obtain treated BaSO4 powder. Add the treated BaSO4 powder into a high-temperature furnace, set the furnace temperature to 700°C, maintain the hydrogen flow rate at 100mL / min, keep the reaction warm for 3 hours, and cool down to 30°C at 4°C / min to obtain gas-doped BaSO4 powder.

[0088] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0089] S3. Calcine the precursor at 700° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0090] Embodiment 11

[0091] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0092] Preparation method:

[0093] S1. Disperse BaSO4 powder in an ethanol solution of 3-chloropropyltriethoxysilane with a mass concentration of 2%, stir to react for 1 hour, filter, and dry at 75°C to obtain treated BaSO4 powder. Add the treated BaSO4 powder into a high-temperature furnace, set the furnace temperature to 700°C, maintain the hydrogen flow rate at 100mL / min, and keep the reaction warm for 3 hours. Then stop the hydrogen supply, maintain the heat treatment at 700°C for 4 hours in an atmospheric atmosphere, cool to 30°C at 4°C / min, wash with deionized water, and dry at 75°C to obtain gas-doped BaSO4 powder.

[0094] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0095] S3. Calcine the precursor at 700° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0096] Example 12

[0097] This embodiment provides a BaSO4-TiO2 composite powder with better structural stability.

[0098] Preparation method:

[0099] S1. Disperse BaSO4 powder in an ethanol solution of 3-chloropropyltriethoxysilane with a mass concentration of 2%, stir to react for 1 hour, filter, and dry at 75°C to obtain treated BaSO4 powder. Add the treated BaSO4 powder into a high-temperature furnace, set the furnace temperature to 700°C, maintain the hydrogen flow rate at 100mL / min, and keep the temperature for 3 hours. Then stop the hydrogen supply, raise the temperature to 900°C in an atmospheric atmosphere and keep the temperature for 2 hours, then cool down to 30°C at 4°C / min, wash with deionized water, and dry at 75°C to obtain gas-doped BaSO4 powder.

[0100] S2. Mix gas-doped BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0101] S3. Calcine the precursor at 700° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0102] Comparative Example 1

[0103] This comparative example provides a relatively conventional BaSO4-TiO2 composite powder

[0104] Preparation method:

[0105] S1. Mix BaSO4 powder and water in a mass ratio of 1:20, heat to 80°C, and adjust the pH to 3 to obtain a BaSO4 suspension; mix TiOSO4 and water in a mass ratio of 1:100 and stir to obtain a TiOSO4 aqueous solution; add the TiOSO4 aqueous solution to the BaSO4 suspension and mix, adjust the pH of the mixed system to 3, stir for 2 hours, and then age at 80°C for 6 hours and at 30°C for 4 hours after stirring. After the reaction is completed, centrifuge, wash, and dry to obtain a precursor, in which the mass ratio of TiOSO4:BaSO4 is 1:6.

[0106] S2. Calcine the precursor at 700° C. in a muffle furnace for 2 h to obtain BaSO4-TiO2 composite powder.

[0107] The composite powders prepared in the above examples and comparative examples were subjected to initial bulk density measurement, and were also subjected to 60 Hz vibration treatment, with a treatment time of 30 min and a vibration amplitude of 10 mm. The bulk density of the composite powders after vibration treatment was measured again, and the specific results are shown in the following table:

[0108]

[0109] It is not difficult to see from the above data that the bulk density of Comparative Example 1 changes significantly after vibration treatment (0.30 g / cm 3 ), while the changes in Examples 1 to 8 were smaller (0.09-0.10 g / cm 3 ). This shows that hydrogen doping significantly improves the structural stability of the powder. It is believed that hydrogen reduces BaSO4 at high temperature to form gas (such as H2O) to generate pores inside the powder. The pores increase the specific surface area of ​​the powder and improve the dispersibility. The pore structure reduces the direct contact area between particles, increases friction and intercalation, and enhances the mechanical stability after stacking.

[0110] The bulk density of Examples 9 to 12 varies (0.03 g / cm 3 ) is significantly smaller than Examples 1 to 8 (0.09-0.10 g / cm 3 ), indicating that the surface coating treatment further improves the structural stability. It is considered that CPTES forms a uniform siloxane coating on the surface of BaSO4 particles through hydrolysis and condensation reactions. The coating provides additional chemical bonding and enhances the interaction between particles. The coating evenly covers the surface of the particles, reduces mechanical friction, and improves the bonding strength between particles.

[0111] Examples 11 and 12 were subjected to additional high temperature treatment (700°C and 900°C) in air atmosphere, and the bulk density change was minimal (0.03 g / cm 3), showing the best structural stability. It is considered that after hydrogen doping and coating treatment, high temperature treatment is further performed to enhance the curing and stability of the coating. High temperature treatment promotes the curing and cross-linking of the coating, increases the stability of the coating and the bonding strength between particles. High temperature treatment helps to eliminate the residual stress inside the particles and in the coating, further improving the mechanical strength and stability of the particles.

[0112] The composite powders prepared in the above Examples 1-6 and Examples 9-12 were respectively used for photocatalytic reactions, and all showed good catalytic activity.

[0113] The composite powders prepared in Examples 7-8 were used for UV-visible light absorption spectrum test, and all showed strong UV absorption and shielding performance; they also showed good pigment performance, with oil absorption and control example (100 μm film thickness) of 22.47 g / 100 g and 83.16%, respectively.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing BaSO4-TiO2 composite powder, characterized in that: The steps include: Step 1: Heat the BaSO4 powder to 600-800°C and keep it warm for 2-4 hours in a hydrogen atmosphere to obtain gas-doped BaSO4 powder; Step 2: prepare the gas-doped BaSO4 powder into a BaSO4 suspension, add the TiOSO4 aqueous solution into the BaSO4 suspension and mix, adjust the pH of the mixed system to 2-4, stir and age at 70-90°C for 3-8h, and age at 20-30°C for 2-6h, centrifuge, wash and dry after the reaction to obtain a precursor, wherein the mass ratio of TiOSO4:BaSO4 is 1:(5-8); Step 3: calcine the precursor in a muffle furnace to obtain BaSO4-TiO2 composite powder.

2. The method for preparing the BaSO4-TiO2 composite powder according to claim 1, characterized in that: In step 1, before heating the BaSO4 powder, the step also includes dispersing the BaSO4 powder in an ethanol solution of 3-chloropropyltriethoxysilane, stirring the reaction for 1-2 hours, and then drying to obtain the treated BaSO4 powder.

3. The method for preparing the BaSO4-TiO2 composite powder according to claim 2, characterized in that: The mass concentration of the 3-chloropropyltriethoxysilane ethanol solution is 1-2%.

4. The method for preparing the BaSO4-TiO2 composite powder according to claim 2, characterized in that: In step 1, after the heat preservation reaction, the BaSO4 powder is heated to 700-900°C, kept warm for 2-4 hours, then cooled to 30°C at 3-4°C / min, washed with deionized water and dried to obtain gas-doped BaSO4 powder.

5. The method for preparing the BaSO4-TiO2 composite powder according to claim 1, characterized in that: In step 2, the BaSO4 suspension is prepared by mixing BaSO4 and water in a mass ratio of 1:(20-40), heating to 70-90°C, and adjusting the pH to 2-4.

6. The method for preparing the BaSO4-TiO2 composite powder according to claim 1, characterized in that: In step 2, the TiOSO4 aqueous solution is obtained by mixing and stirring TiOSO4 and water in a mass ratio of 1:(100-120).

7. The method for preparing the BaSO4-TiO2 composite powder according to claim 1, characterized in that: In step 2, after adjusting the pH of the mixed system to 2-4, stirring is performed for 1-3 hours before aging.

8. The method for preparing the BaSO4-TiO2 composite powder according to claim 1, characterized in that: In step three, the calcination temperature is 600-900° C., and the calcination time is 2 hours.

9. A BaSO4-TiO2 composite powder, characterized in that: The preparation method is described in any one of claims 1 to 8.

10. Use of the BaSO4-TiO2 composite powder according to claim 9 in the field of photocatalysts or pigments.

Citation Information

Patent Citations

  • Preparation method of barium sulfate-carbon aerogel composite support supported palladium catalyst

    CN104741135A

  • Preparation method of barium sulfate for powder coating

    CN106976900A